Performance Evaluation of the Gradient Diffusion Strip Method and Disk Diffusion Method for Ceftazidime–Avibactam Against Enterobacterales and Pseudomonas aeruginosa: A Dual-Center Study - Zhang, Jingjia; Li, Gang; Zhang, Ge; Kang, Wei; Duan, Simeng; Wang, Tong; Li, Jin; Huangfu, Zhiru; Yang, Qiwen; Xu, Yingchun; Jia, Wei; Sun, Hongli (Frontiers in Microbiology, 2021)
Objectives: We evaluated the performance of Etest and the disc diffusion method for the determination of ceftazidime-avibactam against Enterobacterales and P. aeruginosa. Methods: Antimicrobial susceptibility testing of 302 clinical Enterobacterales and P. aeruginosa isolates from two centers were conducted by broth microdilution (BMD), Etest, and disc diffusion method for ceftazidime-avibactam. Using BMD as a gold standard, essential agreement (EA), categorical agreement (CA), major error (ME) and very major error (VME) were determined. CA and EA > 90%, ME < 3%, and VME < 1.5% were considered as acceptable criteria. Polymerase chain reaction and sanger sequencing were performed to determine the carbapenem resistance genes of all the 302 isolates. Results: A total of 302 strains (228 Enterobacterales and 74 P. aeruginosa) were enrolled, among which 182 strains were from center 1 (148 Enterobacterales and 34 P. aeruginosa) and 120 strains were from center 2 (80 Enterobacterales and 40 P. aeruginosa). The CA rates of Etest for Enterobacterales and P. aeruginosa were 100% and 98.65% (73/74), respectively, and the EA rates were 97.37% (222/228) and 98.65% (73/74), respectively. The CArates of the disc diffusion method for Enterobacterales and P. aeruginosa were 100% and 95.95% (71/74), respectively. No very major errors were found by using Etest, while the major error rate was 0.40% (1/247). No major errors were found by using the disc diffusion method, but the very major error rate was 5.45% (3/55). For 31 blaKPC, 33 blaNDM, 7 blaIMP, and 2 blaVIM positive isolates, both of the CA rates and EA rates were 100%, no major error and very major error was detected by two methods. For 15 carbapenemase-non-producing resistance isolates, the CA rate and EA rate of Etest were 100%. Whereas the CA rate of the disc diffusion method was 80.00% (12/15), the very major error rate was 20.00% (3/15). Conclusions: Both Etest and the disc diffusion method can meet the needs of clinical microbiological laboratories for testing the susceptibility of ceftazidime-avibactam drugs. By comparison, the evaluation of Etest was better than that of the disc diffusion method. The detection performance of Enterbacterales was better than that of P. aeruginosa.